Inactivation of SARS-CoV-2 at acidic pH is driven by partial unfolding of spike - Glas, Irina; Zimmermann, Liv; Luo, Beiping; Pohl, Marie O.; Wrobel, Antoni G.; Schaub, Aline; Klein, Liviana K.; David, Shannon C.; Gaggioli, Elisabeth; Bluvshtein, Nir; Huber, Michael; Nenes, Athanasios; et al. (Communications biology, 2025)
SARS-CoV-2, the causative agent of COVID-19, is predominantly transmitted by respiratory aerosol and contaminated surfaces. Recent studies demonstrated that aerosols can become acidic, and acidification has been proposed as decontamination method. Here, we investigate how SARS-CoV-2 reacts to acidic pH and by which mechanism the virus is inactivated. We show that a pH below 3 is required to inactivate SARS-CoV-2 in a period of seconds to minutes. While we measured a 1000 to 10,000-fold drop in infectivity, virion structure remained intact under these conditions. Using super-resolution microscopy, we found that the attachment of virions to target cells is abrogated after acidic treatment, revealing spike protein (S) as the major inactivation target. Limited proteolysis of S combined with testing spike-specific antibodies for binding under low pH conditions revealed that exposure of SARS-CoV-2 to pH below 3 results in partial unfolding of S, thereby preventing binding of virions to target cells.